The Chinese version of the cognitive, affective, and somatic empathy scale for children: Validation, gender invariance and associated factors - Liu, Jianghong (PLoS One, 2018)
OBJECTIVES: Empathy is hypothesized to have several components, including affective, cognitive, and somatic contributors. The only validated, self-report measure to date that assesses all three forms of empathy is the Cognitive, Affective, and Somatic Empathy Scale (CASES), but no current study has reported the psychometric properties of this scale outside of the initial U.S. sample. This study reports the first psychometric analysis of a non-English translation of the CASES. METHODS: Confirmatory factor analysis was used to assess the factor structure of CASES as well as its associations with callous-unemotional traits in 860 male and female children (mean age 11.54± .64 years) from the China Jintan Child Cohort Study. RESULTS: Analyses supported a three-factor model of cognitive, affective, and somatic empathy, with satisfactory fit indices consistent with the psychometric properties of the English version of CASES. Construct validity was established by three findings. First, females scored significantly higher in empathy than males. Second, lower scores of empathy were associated with lower IQ. Third, children with lower empathy also showed more callous-unemotional attributes. CONCLUSIONS: We established for the first time cross-cultural validity for Cognitive, Affective, and Somatic Empathy Scale (CASES). Our Chinese data supports the use of this new instrument in non-Western samples, and affirms the utility of this instrument for a comprehensive assessment of empathy in children.